Microbial diversity and community assembly in heavy metal-contaminated soils: insights from selenium-impacted mining areas - Wang, Zhiyong; Deng, Guangai; Hu, Chongyang; Hou, Xue; Zhang, Xinyuan; Fan, Zhiquan; Zhao, Yong; Peng, Mu (Frontiers in Microbiology, 2025)
The mining industry in China plays a pivotal role in economic development but also leads to severe environmental issues, particularly heavy metal pollution in soils. Heavy metal pollution significantly impacts soil microbial communities due to its persistence and long-term residual effects. We assessed changes in microbial diversity, community structure, and assembly mechanisms in selenium-impacted soils. This study investigates the impacts of selenium (Se) and other heavy metals on soil microbial communities in selenium-rich mining areas using full-length 16S rRNA gene sequencing. Our results showed that Se and other heavy metal contamination significantly altered microbial community composition, favoring metal-tolerant phyla such as Proteobacteria, Actinobacteriota and Firmicutes, while reducing the abundance of sensitive groups like Acidobacteriota and Chloroflexi. Microbial diversity decreased as Se and other heavy metal concentrations increased. Mantel test analysis revealed that soil total potassium (TK), soil organic carbon, total nitrogen, and several other metals, including zinc, niobium, titanium (Ti), manganese, rubidium, barium, potassium, cobalt, gallium (Ga), Se, chromium (Cr), vanadium, and copper were significantly and positively correlated with microbial community composition across all soil samples. Random forest analysis showed that soil TK and multiple elements [Cr, Ti, nickel (Ni), Ga and Se] were the most important predictors of bacterial diversity, emphasizing the role of multiple elements in shaping microbial communities. Co-occurrence network analysis revealed that Se and other heavy metal contamination reduced network complexity and stability, with high Se-contaminated soils exhibiting fragmented microbial networks. Community assembly was primarily driven by drift in control soils, whereas dispersal limitation became more prominent in Se-contaminated soils due to heavy metal toxicity. These findings highlight the ecological consequences of heavy metal pollution on microbial communities and offer valuable insights for effective soil management and remediation strategies.